Stability and dynamics in an overlapping generations economy under flexible wage negotiation and capital accumulation - Erkki Koskela; Mikko Puhakka (Center for Economic Studies and ifo Institute (CESifo), 2006)
We analyze the stability and dynamics of an overlapping generations model under imperfectly competitive labour markets without population growth and with perfect foresight. Under right-to-manage wage bargaining we assume that wage is negotiated after the decision on the capital stock. With Cobb-Douglas utility and production functions the steady state is unique and the steady state capital stock depends on the trade union's bargaining power. This is because higher bargaining power of the trade union will induce workers to save more thus boosting the capital stock, ceteris paribus. Finally, we show that the steady state equilibrium is a saddle point.
Keywords: J51; C62; 330